Identification of a biomarker for sleep drive in flies and humans. - Seugnet, L.; Boero, J.; Gottschalk, L.; Duntley, S.P.; Shaw, P.J. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
It is a common experience to sacrifice sleep to meet the demands of our 24-h society. Current estimates reveal that as a society, we sleep on average 2 h less than we did 40 years ago. This level of sleep restriction results in negative health outcomes and is sufficient to produce cognitive deficits and reduced attention and is associated with increased risk for traffic and occupational accidents. Unfortunately, there is no simple quantifiable marker that can detect an individual who is excessively sleepy before adverse outcomes become evident. To address this issue, we have developed a simple and effective strategy for identifying biomarkers of sleepiness by using genetic and pharmacological tools that dissociate sleep drive from wake time in the model organism Drosophila melanogaster. These studies have identified a biomarker, Amylase, that is highly correlated with sleep drive. More importantly, both salivary Amylase activity and mRNA levels are also responsive to extended waking in humans. These data indicate that the fly is relevant for human sleep research and represents a first step in developing an effective method for detecting sleepiness in vulnerable populations.